Cost-effectiveness of Tdap vaccination of adults aged ≥65 years in the prevention of pertussis in the US: a dynamic model of disease transmission. - Lisa J McGarry (PLoS ONE, 2014)
OBJECTIVES: In February 2012, the Advisory Committee on Immunization Practices (ACIP) advised that all adults aged ≥65 years receive a single dose of reduced-antigen-content tetanus, diphtheria, and acellular pertussis (Tdap), expanding on a 2010 recommendation for adults >65 that was limited to those with close contact with infants. We evaluated clinical and economic outcomes of adding Tdap booster of adults aged ≥65 to "baseline" practice [full-strength DTaP administered from 2 months to 4-6 years, and one dose of Tdap at 11-64 years replacing decennial Td booster], using a dynamic model. METHODS: We constructed a population-level disease transmission model to evaluate the cost-effectiveness of supplementing baseline practice by vaccinating 10% of eligible adults aged ≥65 with Tdap replacing the decennial Td booster. US population effects, including indirect benefits accrued by unvaccinated persons, were estimated during a 1-year period after disease incidence reached a new steady state, with consequences of deaths and long-term pertussis sequelae projected over remaining lifetimes. Model outputs include: cases by severity, encephalopathy, deaths, costs (of vaccination and pertussis care) and quality-adjusted life-years (QALYs) associated with each strategy. Results in terms of incremental cost/QALY gained are presented from payer and societal perspectives. Sensitivity analyses vary key parameters within plausible ranges. RESULTS: For the US population, the intervention is expected to prevent >97,000 cases (>4,000 severe and >5,000 among infants) of pertussis annually at steady state. Additional vaccination costs are $4.7 million. Net cost savings, including vaccination costs, are $47.7 million (societal perspective) and $44.8 million (payer perspective). From both perspectives, the intervention strategy is dominant (less costly, and more effective by >3,000 QALYs) versus baseline. Results are robust to sensitivity analyses and alternative scenarios. CONCLUSIONS: Immunization of eligible adults aged ≥65, consistent with the current ACIP recommendation, is cost saving from both payer and societal perspectives.